TINJAUAN FIQH SIYASAH DAN UNDANG-UNDANG NOMOR 23 TAHUN 2014 (STUDI KASUS KANTOR CAMAT CANDI, SIDOARJO): Review of Siyasah Fiqh and Law Number 23 of 2014 (Case Study of Candi Subdistrict Office, Sidoarjo) - Larasati Fitriani Asis (Constitution Journal, 2022)
This study aims to determine the implementation of the duties and authorities of the Candi Camat in coordinating village government as well as a review of Fiqh Siyasah and Law Number 23 of 2014 concerning Regional Government on the implementation of the duties and authorities of the Candi Camat in coordinating village government in Candi District, Sidoarjo Regency. The type of research is field research (field research) and using a qualitative approach. Then, the data collection methods used in this study were observation, interviews, and documentation and the validity of the triangulation data sources. From the results of research using indicators 1) Coordinate community empowerment, 2) Coordinate efforts to organize public peace and order; 3) Coordinate the implementation and enforcement of Regional Regulations and Regional Regulations; 4) Coordinate the maintenance of public service infrastructure and facilities; 5) Coordinate the implementation of government activities carried out by regional officials in the sub-district; and 6) Fostering and supervising the implementation of village and/or kelurahan activities, showing that the Candi Camat implements his duties and authorities in accordance with Law Number 23 of 2014 concerning Regional Government and also applies the leadership of Fiqh Siyasah, which is more precisely leadership that must be imitated from the Prophet Muhammad SAW namely siddiq, amanah, fathanah, and tabligh. The Candi Camat is quite good at coordinating his duties and authorities, but the Candi Camat needs to improve his relationship with the community in terms of village development, as well as provide maximum guidance to all levels of society in terms of community empowerment in Candi Subdistrict.     Penelitian ini bertujuan untuk mengetahui implementasi tugas dan wewenang Camat Candi dalam mengkoordinasikan pemerintahan desa serta tinjauan Fiqh Siyasah dan Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah terhadap implementasi tugas dan wewenang Camat Candi dalam mengkoordinasikan pemerintahan desa di Kecamatan Candi, Kabupaten Sidoarjo. Jenis penelitian yaitu penelitian lapangan (field research) dan menggunakan pendekatan kualitatif. Kemudian, metode pengumpulan data yang digunakan dalam penelitian ini yaitu, observasi, wawancara, dan dokumentasi dan keabsahan data triangulasi sumber. Dari hasil penelitian yang menggunakan indikator 1) Mengkoordinasikan pemberdayaan masyarakat, 2) Mengoordinasikan upaya penyelenggaraan ketenteraman dan ketertiban umum; 3) Mengoordinasikan penerapan dan penegakan Perda dan Perkada; 4) Mengoordinasikan pemeliharaan prasarana dan sarana pelayanan umum; 5) Mengoordinasikan penyelenggaraan kegiatan pemerintahan yang dilakukan oleh perangkat daerah di kecamatan; dan 6) Membina dan mengawasi penyelenggaraan kegiatan desa dan/atau kelurahan,  menunjukkan bahwa Camat Candi dalam mengimplementasikan tugas dan wewenang sesuai dengan Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah dan juga menerapkan kepemimpinan Fiqh Siyasah yang lebih tepatnya kepemimpinan yang harus diteladani dari Nabi Muhammad SAW yaitu siddiq, amanah, fathanah, dan tabligh. Camat Candi sudah cukup baik dalam mengkoordinasikan tugas dan wewenangnya, namun Camat Candi perlu meningkatkan hubungannya dengan masyarakat dalam hal pembangunan desa, serta memberikan pembinaan yang maksimal kepada seluruh lapisan masyarakat dalam hal pemberdayaan masyarakat di Kecamatan Candi.